Wear-resistant porcelain tile with a silver sand effect on the surface and method for manufacturing same
Patent Information
- Application Number
- CN202411476790.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-10-22
AI Technical Summary
但是该黑金砂抛釉的施釉量是普通抛釉的1.5~2.5倍,且需要透感好才能呈现金砂效果,所以黑金砂抛釉烧后会有大量的玻璃相,使得抛后釉面耐磨性能极差,而且大量的三氧化二铁也会降低釉面的耐磨性能
[0004] To address the aforementioned problems, this invention provides a wear-resistant ceramic tile with a silver sand effect on its surface and its preparation method. After firing, the tile surface develops a silver sand effect that gradually intensifies. This decorative effect differs from the superficial glitter effects found in some commercially available products; the overall surface of the wear-resistant ceramic tile possesses a silvery metallic luster that gradually strengthens, creating a stunning visual effect and enhancing the product's decorative performance. Furthermore, the preparation method of this invention eliminates the need for inkjet printing, saving on the cost of inkjet printing equipment and ink, significantly reducing production costs, simplifying the manufacturing process, and achieving a technological breakthrough.
Smart Images

Figure CN119330752B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building ceramics, specifically to a wear-resistant porcelain tile with a silver sand effect on its surface and its preparation method. Background Technology
[0002] With the development of the building ceramics market, the variety of building decoration materials is increasing, and consumers are placing higher demands on the material, pattern layering, color, and decorative effect of tiles. Artistic glazes from everyday ceramics are highly favored by consumers due to their unique artistic style. Many manufacturers have begun to apply these artistic glazes from everyday ceramics to building ceramics. However, because artistic glazes from everyday ceramics require long periods of heat preservation to crystallize, they are difficult to adapt to the low-temperature, rapid firing process required for building ceramics.
[0003] Chinese patent CN2017111166511.0 discloses a glaze for imitating the effect of black gold sand marble and its application. The glaze for imitating the effect of black gold sand marble consists of a sand crystal protective glaze, mica iron oxide, ceramic stamping paste, and polishing glaze. Through the combination of mica iron oxide, sand crystal protective glaze, and black gold sand polishing glaze, a superior gold sand effect is achieved on ceramic tiles. However, the amount of glaze applied to this black gold sand polishing glaze is 1.5 to 2.5 times that of ordinary polishing glaze, and it requires good transparency to achieve the gold sand effect. Therefore, after firing, the black gold sand polishing glaze contains a large amount of glass phase, resulting in extremely poor wear resistance of the glaze surface after polishing. Furthermore, the large amount of ferric oxide also reduces the wear resistance of the glaze surface. Summary of the Invention
[0004] To address the aforementioned problems, this invention provides a wear-resistant ceramic tile with a silver sand effect on its surface and its preparation method. After firing, the tile surface develops a silver sand effect that gradually intensifies. This decorative effect differs from the superficial glitter effects found in some commercially available products; the overall surface of the wear-resistant ceramic tile possesses a silvery metallic luster that gradually strengthens, creating a stunning visual effect and enhancing the product's decorative performance. Furthermore, the preparation method of this invention eliminates the need for inkjet printing, saving on the cost of inkjet printing equipment and ink, significantly reducing production costs, simplifying the manufacturing process, and achieving a technological breakthrough.
[0005] In a first aspect, the present invention provides a method for preparing a wear-resistant ceramic tile with a silver sand effect on its surface. The preparation method includes the following steps: Apply silver sand glaze to the surface of the brick blank; Apply silver sand metallic dry granule glaze to the surface of the brick blank after applying silver sand glaze; After applying a dry granular glaze of silver sand, the brick blank is fired and polished to obtain a wear-resistant porcelain tile with a silver sand effect on the surface.
[0006] Preferably, the mineral composition of the silver sand metal dry granule glaze includes flaky mica iron oxide and silver sand metal dry granules; wherein the mass ratio of flaky mica iron oxide to silver sand metal dry granules is (5-10):(90-95).
[0007] Preferably, the chemical composition of the silver sand dry metal particles includes, by mass percentage: loss on ignition: 0.5%–0.8%; Al2O3: 14.2%–18.5%; SiO2: 40.1%–49.3%; Fe2O3: 10.4%–19.6%; CaO: 1.2%–4.3%; MgO: 0.05%–0.5%; K2O: 1.2%–4.4%; Na2O: 1.6%–3.8%; TiO2: 2.5%–4.5%; ZnO: 2.4%–4.8%; P2O5: 7.2%–14.2%; Li2O: 1.4%–3.6%; CaF2: 2.1%–4.3%.
[0008] Preferably, the aspect ratio of the flaky mica iron oxide is 65 to 110.
[0009] Preferably, the chemical composition of the silver sand metallic dry granule glaze includes, by mass percentage: loss on ignition: 0.6%–1.0%; Al2O3: 12.3%–16.2%; SiO2: 36.2%–46.6%; Fe2O3: 15.7%–25.9%; CaO: 1.2%–3.6%; MgO: 0.05%–0.5%; K2O: 1.4%–3.2%; Na2O: 1.3%–2.8%; TiO2: 1.9%–4.1%; ZnO: 2.1%–4.2%; P2O5: 6.5%–12.5%; Li2O: 1.2%–3.4%; CaF2: 1.8%–3.9%.
[0010] Preferably, the silver sand metallic dry granule glaze is applied by pouring; more preferably, the specific gravity of the silver sand metallic dry granule glaze is 1.30–1.34 g / cm³. 3 The glaze application amount is 750-860 g / m². 2 .
[0011] Preferably, the mineral composition of the silver sand metal dry particles includes, by mass percentage: 20%–30% potassium feldspar, 10%–20% washed kaolin, 20%–30% quartz, 20%–40% iron phosphate, 5%–10% fluorite, 4%–10% zinc oxide, 6%–8% spodumene, and 4%–6% rutile.
[0012] Preferably, the mineral composition of the silver sand glaze includes a zirconium-free glaze and a cobalt black pigment, wherein the mass ratio of the zirconium-free glaze to the cobalt black pigment is 100:(2-5).
[0013] Preferably, the chemical composition of the zirconium-free glaze includes, by mass percentage: loss on ignition: 1.2%–1.8%; SiO2: 56.4%–60.6%; Al2O3: 28.2%–32.3%; CaO: 0.6%–0.9%; MgO: 0.3%–0.5%; K2O: 3.1%–5.2%; Na2O: 3.2%–4.8%; preferably, the mineral composition of the zirconium-free glaze includes, by mass percentage: potassium feldspar 35%–45%, sodium feldspar 0.1%–5%, nepheline 20%–35%, washed kaolinite 8%–12%, quartz 5%–10%, and calcined alumina 15%–20%.
[0014] Preferably, the chemical composition of the silver sand glaze includes, by mass percentage: loss on ignition: 1.4%–2.2%; SiO2: 55.4%–62.3%; Al2O3: 27.8%–31.5%; CaO: 0.6%–1.0%; MgO: 0.2%–0.4%; K2O: 3.2%–5.7%; Na2O: 3.2%–5.8%; CoO: 2.5%–4%.
[0015] Preferably, the silver sand glaze is applied by pouring glaze; more preferably, the specific gravity of the silver sand glaze is 1.82–1.86 g / cm³. 3 The glaze application rate is 600-700 g / m². 2 .
[0016] Preferably, the maximum firing temperature is 1180–1200℃ and the firing time is 40–50 minutes.
[0017] Secondly, the present invention provides a wear-resistant ceramic tile with a silver sand effect on its surface. The wear-resistant ceramic tile with the silver sand effect is obtained according to the aforementioned preparation method. Attached Figure Description
[0018] Figure 1 This is a rendering of the surface of the porcelain tile from Example 1; Figure 2 This is a rendering of the surface of the porcelain tile from Example 2. Detailed Implementation
[0019] The present invention is further illustrated by the following embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the present invention. Unless otherwise specified, all percentage contents refer to mass percentage contents. The following exemplarily illustrates a method for preparing the wear-resistant porcelain tile with a silver sand effect on the surface according to the present invention.
[0020] The green body powder is pressed into shape to obtain brick blanks. Green body powder commonly used in the art can be used. As an example, the chemical composition of the green body powder includes, by mass percentage: loss on ignition: 3.7%–4.5%; SiO2: 67.8%–69.5%; Al2O3: 17.2%–19.6%; Fe2O3: 0.5%–0.8%; TiO2: 0.1%–0.3%; CaO: 0.4%–0.7%; MgO: 0.3%–0.8%; K2O: 2.8%–3.9%; Na2O: 2.2%–2.8%.
[0021] The green body can be prepared using ceramic raw materials commonly used in this field. The raw material is ball-milled, spray-granulated, and pressed to obtain a brick green body. The powder can be applied within the mold cavity of a press for pressing. The moisture content of the green body powder is preferably controlled between 7.0 wt% and 7.6 wt%. As an example, the particle size of the green body powder includes, by mass percentage: <2% residue on a 20-mesh sieve, 30%–40% residue on a 40-mesh sieve, 75%–85% residue on a 60-mesh sieve, and >92% residue on a 100-mesh sieve; the residue values for each mesh size are cumulative.
[0022] Dry the brick blanks. Drying can be carried out in a drying kiln. The moisture content of the dried brick blanks should be controlled within 0.2wt% to 0.3wt%.
[0023] A silver-frosted glaze is applied to the surface of the brick blank to form a surface glaze layer. The surface of the dried brick blank can be cleaned before applying the silver-frosted glaze.
[0024] The mineral composition of the silver sand glaze includes a zirconium-free glaze and a cobalt black pigment. The mass ratio of the zirconium-free glaze to the cobalt black pigment is 100:(2-5). This combination of zirconium-free glaze and cobalt black pigment results in a grayish-black glaze surface after firing. Applying subsequent dry-grained silver sand glaze over this surface creates an effect similar to a black sky with a silver sheen, enhancing the silver sand effect. Furthermore, zirconium-containing glazes, due to their higher whiteness, produce a poorer silver sand effect and also increase costs.
[0025] The chemical composition of the zirconium-free glaze includes, by mass percentage: loss on ignition: 1.2%–1.8%; SiO2: 56.4%–60.6%; Al2O3: 28.2%–32.3%; CaO: 0.6%–0.9%; MgO: 0.3%–0.5%; K2O: 3.1%–5.2%; Na2O: 3.2%–4.8%.
[0026] As an example, the mineral composition of the zirconium-free glaze includes, by mass percentage: 35%–45% potassium feldspar, 0%–5% sodium feldspar (preferably 0.1%–5%), 20%–35% nepheline, 8%–12% washed kaolin, 5%–10% quartz, and 15%–20% calcined alumina.
[0027] In some technical solutions, the chemical composition of the silver sand glaze may include: by mass percentage, loss on ignition: 1.4%–2.2%; SiO2: 55.4%–62.3%; Al2O3: 27.8%–31.5%; CaO: 0.6%–1.0%; MgO: 0.2%–0.4%; K2O: 3.2%–5.7%; Na2O: 3.2%–5.8%; CoO: 2.5%–4%.
[0028] Water and additives can be added to the mineral composition of the silver sand glaze to adjust it to the desired specific gravity. The additives include sodium tripolyphosphate and sodium carboxymethyl cellulose. Sodium carboxymethyl cellulose can account for 0.1wt% to 0.4wt% of the mineral composition of the silver sand glaze, and sodium tripolyphosphate can account for 0.1wt% to 0.4wt% of the mineral composition of the silver sand glaze. In actual production, water can be added to the glaze slurry of the silver sand glaze to adjust it to the desired specific gravity.
[0029] The silver-sand glaze can be applied by pouring. Preferably, the specific gravity of the silver-sand glaze is 1.82–1.86 g / cm³. 3 The glaze application rate is 600-700 g / m². 2 The glazing parameters for silver sand glaze are controlled within this range, which can cover the blemishes on the surface of the brick and also help control the shape of the brick.
[0030] The brick blanks with the silver-flecked glaze are dried. This helps to remove as much moisture as possible from the glaze layer. Electric kiln drying can be used. For example, the drying temperature is 250–280℃, and the drying time is 120–240 seconds.
[0031] A silver-sand metallic dry-granule glaze is applied to the surface of the tile after the silver-sand glaze has been applied. The mineral composition of the silver-sand metallic dry-granule glaze includes flaky mica iron oxide and silver-sand metallic dry particles. Flaky mica iron oxide itself possesses a strong silvery metallic luster, while the silver-sand metallic dry particles, after firing, precipitate crystals with a silvery metallic luster, resulting in a relatively weaker metallic luster. The two complement each other, creating a gradient of silvery metallic luster on the tile surface, from weak to strong and vice versa, resulting in a stunning visual effect. The mass ratio of flaky mica iron oxide to silver-sand metallic glaze is (5-10):(90-95). Too low a content of flaky mica iron oxide results in a weak silver-sand effect on the surface. Too high a content, while producing a strong silver-sand effect, leads to excessively high production costs. If only mica iron oxide is used, the glaze can only achieve a shimmering effect, not a full-surface metallic luster.
[0032] Preferably, the aspect ratio of the flaky mica iron oxide is 65-110. If granular mica iron oxide with a small aspect ratio is used, the silvery metallic luster is weak, requiring a large amount of mica iron oxide. However, the main component of mica iron oxide is α-Fe₂O₃, which is a flux; excessive mica iron oxide will produce a large amount of glassy phase, reducing the wear resistance of the ceramic tile surface. This invention uses flaky mica iron oxide with a large aspect ratio, which provides a strong silvery metallic luster, and only a small amount is needed to meet the requirements. Therefore, using flaky mica iron oxide instead of granular mica iron oxide can improve the silver sand effect of the glaze without affecting its wear resistance.
[0033] In some technical solutions, the chemical composition of the silver sand metal particles includes, by mass percentage, loss on ignition: 0.5%–0.8%; Al2O3: 14.2%–18.5%; SiO2: 40.1%–49.3%; Fe2O3: 10.4%–19.6%; CaO: 1.2%–4.3%; MgO: 0.05%–0.5%; K2O: 1.2%–4.4%; Na2O: 1.6%–3.8%; TiO2: 2.5%–4.5%; ZnO: 2.4%–4.8%; P2O5: 7.2%–14.2%; Li2O: 1.4%–3.6%; CaF2: 2.1%–4.3%. TiO2 and ZnO are crystallizing agents, while Li2O and CaF2 are fluxing agents, which can also promote crystallization, resulting in the precipitation of a large amount of Fe2O3 and crystalline iron-aluminum spinel on the surface. This gives the fired glaze a metallic luster and also improves the wear resistance of the glaze. Al2O3 is introduced by nano-corundum, which further improves the wear resistance of the glaze.
[0034] As an example, the mineral composition of the silver sand dry particles includes, by mass percentage: 20%–30% potassium feldspar, 10%–20% washed kaolin, 20%–30% quartz, 20%–40% iron phosphate, 5%–10% fluorite, 4%–10% zinc oxide, 6%–8% spodumene, and 4%–6% rutile.
[0035] If the mineral composition of flaky mica iron oxide and silver sand dry metal particles is directly mixed and used, the glaze after firing will be almost entirely glassy, with poor wear resistance and no granular texture on the surface.
[0036] In some technical solutions, the chemical composition of the silver sand metallic dry granule glaze includes: by mass percentage, loss on ignition: 0.6%–1.0%; Al2O3: 12.3%–16.2%; SiO2: 36.2%–46.6%; Fe2O3: 15.7%–25.9%; CaO: 1.2%–3.6%; MgO: 0.05%–0.5%; K2O: 1.4%–3.2%; Na2O: 1.3%–2.8%; TiO2: 1.9%–4.1%; ZnO: 2.1%–4.2%; P2O5: 6.5%–12.5%; Li2O: 1.2%–3.4%; CaF2: 1.8%–3.9%. The chemical composition of the aforementioned silver sand metal dry granule glaze refers to the chemical composition of the mineral materials in the silver sand metal dry granule glaze, that is, the chemical composition of other raw materials (specifically, mica iron oxide and silver sand metal dry granules) that do not contain auxiliary materials.
[0037] A glaze slurry for preparing a dry-particle silver sand metallic glaze is prepared. In addition to flaky mica iron oxide and dry-particle silver sand, the glaze slurry also includes 210 wt% to 220 wt% of auxiliary materials (suspending agents) comprising the dry-particle silver sand. As an example, the auxiliary materials include, by weight, 30-40 parts sodium carboxymethyl cellulose, 16-27 parts glycerol, 20-30 parts ethylene glycol, 3-5 parts preservative, and 20-30 parts water.
[0038] The silver sand metallic dry granule glaze can be applied by pouring. Preferably, the specific gravity of the silver sand metallic dry granule glaze is 1.30–1.34 g / cm³. 3 The glaze application amount is 750-860 g / m². 2 The specific gravity of the silver-sand metallic dry granule glaze within this range is beneficial for the uniformity of glazing. If the specific gravity of the silver-sand metallic dry granule glaze is too low, the glaze curtain is prone to floating, resulting in bell-shaped defects; if the specific gravity is too high, air bubbles are prone to forming, causing glaze pit defects. If the amount of silver-sand metallic dry granule glaze applied is too small, the glaze surface crystallization is difficult, resulting in a weak silver-sand effect on the surface of the prepared porcelain tile samples; if the amount of silver-sand metallic dry granule glaze applied is too large, the prepared porcelain tile samples are too round, exceeding the standard, and also increase production costs.
[0039] If dry silver sand particles and transparent polished glaze are mixed, a large amount of glaze is needed to achieve the gold sand effect with high transparency. After firing, the glaze surface has a large amount of glass phase, many pores, and extremely poor wear resistance after polishing.
[0040] Firing. The ceramic tile is placed in a kiln for firing. The maximum firing temperature is 1180℃~1200℃, and the firing time is 40 minutes~50 minutes. If the firing temperature is too low, although the ceramic tile surface will have a silver sand effect, the surface will be rough and its stain resistance will be poor; if the firing temperature is too high, the dry silver sand metal particles will not be able to crystallize, resulting in a poor silver sand effect on the surface.
[0041] Polishing. Preferred is a fine brush. As an example, the fine brush blocks are arranged in a 5-group abrasive brush configuration.
[0042] Edge grinding and packaging.
[0043] The method for preparing wear-resistant porcelain tiles with a silver sand effect described in this invention produces a silver sand effect on the tile surface after firing, ranging from weak to strong. This decorative effect differs from the glittery products on the market that only offer partial embellishment; the entire surface of the silver sand porcelain tile has a silvery metallic luster, gradually increasing in intensity, creating a stunning visual effect and enhancing the product's decorative performance. The wear-resistant porcelain tiles with a silver sand effect described in this invention have an wear resistance level of 4 at 6000 revolutions; a stain resistance level of 5; and a silver sand glaze gloss of 4-8 degrees after firing. Furthermore, due to the color addition to the surface glaze and the inherent color effect of the silver sand metallic dry particles and flaky mica iron oxide, inkjet printing is unnecessary after applying the silver sand glaze, saving on the cost of purchasing inkjet printing equipment and ink, and significantly reducing production costs.
[0044] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values in the examples below.
[0045] The stain resistance performance was tested in accordance with the standard GB / T 3810.14-2016.
[0046] Wear resistance was tested in accordance with the standard GB / T 3810.7-2016.
[0047] Example 1
[0048] The preparation method of wear-resistant ceramic tiles with a silver sand effect includes the following steps:
[0049] Step 1. Press the green body powder into shape to obtain a brick blank.
[0050] Step 2. Apply a silver-sand glaze to the dried brick surface. The mineral composition of the silver-sand glaze includes a zirconium-free glaze and cobalt black pigment, wherein the mass ratio of the zirconium-free glaze to the cobalt black pigment is 100:3. The chemical composition of the zirconium-free glaze includes, by mass percentage: loss on ignition: 1.8%; SiO2: 58.2%; Al2O3: 30.8%; CaO: 0.8%; MgO: 0.3%; K2O: 3.8%; Na2O: 4.3%. The mineral composition of the zirconium-free glaze includes, by mass percentage: potassium feldspar 40%, sodium feldspar 5%, nepheline 25%, washed kaolin 9%, quartz 5%, and calcined alumina 16%. The chemical composition of the silver sand glaze includes, by mass percentage: Loss on ignition: 1.8%; SiO2: 56.6%; Al2O3: 29.8%; CaO: 0.8%; MgO: 0.3%; K2O: 3.3%; Na2O: 4.6%; CoO: 2.8%. The silver sand glaze is applied by pouring, and its specific gravity is 1.84 g / cm³. 3 Glazing amount is 650g / m 2 .
[0051] Step 3. Apply silver sand metallic dry granule glaze to the surface of the brick after applying the silver sand glaze. The mineral composition of the silver sand metallic dry granule glaze includes flaky mica iron oxide and silver sand metallic dry granules, wherein the mass ratio of flaky mica iron oxide to silver sand metallic dry granules is 5:95. The chemical composition of the flaky mica iron oxide includes, by mass percentage: Fe2O3: 99.45%; SiO2: 0.55%. The aspect ratio of the flaky mica iron oxide is 80. The chemical composition of the silver abrasive metal particles includes, by mass percentage: Loss on ignition: 0.6%; Al2O3: 14.2%; SiO2: 41.3%; Fe2O3: 16.8%; CaO: 2.4%; MgO: 0.2%; K2O: 3.1%; Na2O: 2.4%; TiO2: 3.2%; ZnO: 2.8%; P2O5: 7.8%; Li2O: 2.5%; CaF2: 2.7%. The mineral composition of the silver abrasive metal particles includes, by mass percentage: 20% potassium feldspar, 10% washed kaolin, 20% quartz, 30% iron phosphate, 6% fluorite, 4% zinc oxide, 6% spodumene, and 4% rutile. The chemical composition of the silver sand metallic dry granule glaze includes, by mass percentage: Loss on ignition: 0.7%; Al2O3: 13.5%; SiO2: 39.3%; Fe2O3: 20.9%; CaO: 2.3%; MgO: 0.2%; K2O: 2.9%; Na2O: 2.3%; TiO2: 3.0%; ZnO: 2.6%; P2O5: 7.4%; Li2O: 2.4%; CaF2: 2.5%. The silver sand metallic dry granule glaze is applied by pouring, with a specific gravity of 1.34 g / cm³. 3 Glazing amount is 750g / m2 .
[0052] Step 4. Place the brick blanks, after applying the silver sand metallic dry granule glaze, into the kiln for firing. The firing ring temperature is 1185℃, and the firing time is 45 minutes.
[0053] Step 5. Fine polishing, edge grinding, grading, and packaging. Install 6 sets of grinding brushes for fine polishing.
[0054] Figure 1 This is a rendering of the surface of the porcelain tile from Example 1. From... Figure 1 It can be seen that the surface of the porcelain tile sample has a silver sand effect. Furthermore, the porcelain tile sample prepared in Example 1 has a delicate feel. Tested by the National Ceramic and Plumbing Products Quality Inspection and Testing Center, its stain resistance is level 5, its wear resistance is level 4 at 6000 revolutions, and the water absorption rate of the tile after firing is less than 0.5 wt%.
[0055] Example 2
[0056] The preparation method of wear-resistant ceramic tiles with a silver sand effect includes the following steps:
[0057] Step 1. Press the green body powder into shape to obtain a brick blank.
[0058] Step 2. Apply a silver-sand glaze to the dried brick surface. The mineral composition of the silver-sand glaze includes a zirconium-free glaze and cobalt black pigment, wherein the mass ratio of the zirconium-free glaze to the cobalt black pigment is 100:4. The chemical composition of the zirconium-free glaze includes, by mass percentage: loss on ignition: 1.5%; SiO2: 58.5%; Al2O3: 30.2%; CaO: 0.7%; MgO: 0.4%; K2O: 4.4%; Na2O: 4.3%. The mineral composition of the zirconium-free glaze includes, by mass percentage: potassium feldspar 40%, sodium feldspar 5%, nepheline 25%, washed kaolin 9%, quartz 6%, and calcined alumina 15%. The chemical composition of the silver sand glaze includes, by mass percentage: Loss on ignition: 1.5%; SiO2: 55.6%; Al2O3: 29.8%; CaO: 0.8%; MgO: 0.3%; K2O: 3.6%; Na2O: 4.6%; CoO: 3.8%. The silver sand glaze is applied by pouring, and its specific gravity is 1.84 g / cm³. 3 Glazing amount is 650g / m 2 .
[0059] Step 3. Apply silver sand metallic dry granule glaze to the surface of the brick after applying the silver sand glaze. The mineral composition of the silver sand metallic dry granule glaze includes flaky mica iron oxide and silver sand metallic dry granules, wherein the mass ratio of flaky mica iron oxide to silver sand metallic dry granules is 10:90. The chemical composition of the flaky mica iron oxide includes, by mass percentage: Fe2O3: 99.45%; SiO2: 0.55%. The aspect ratio of the flaky mica iron oxide is 80. The chemical composition of the silver abrasive metal particles includes, by mass percentage: Loss on ignition: 0.6%; Al2O3: 14.2%; SiO2: 41.3%; Fe2O3: 16.8%; CaO: 2.4%; MgO: 0.2%; K2O: 3.1%; Na2O: 2.4%; TiO2: 3.2%; ZnO: 2.8%; P2O5: 7.8%; Li2O: 2.5%; CaF2: 2.7%. The mineral composition of the silver abrasive metal particles includes, by mass percentage: 20% potassium feldspar, 10% washed kaolin, 20% quartz, 30% iron phosphate, 6% fluorite, 4% zinc oxide, 6% spodumene, and 4% rutile. The chemical composition of the silver sand metallic dry granule glaze includes, by mass percentage: Loss on ignition: 0.6%; Al2O3: 12.4%; SiO2: 36.8%; Fe2O3: 25.8%; CaO: 2.1%; MgO: 0.2%; K2O: 2.8%; Na2O: 2.2%; TiO2: 2.8%; ZnO: 2.5%; P2O5: 7.1%; Li2O: 2.3%; CaF2: 2.4%. The silver sand metallic dry granule glaze is applied by pouring, with a specific gravity of 1.34 g / cm³. 3 Glazing amount is 850g / m 2 .
[0060] Step 4. Place the brick blanks, after applying the silver sand metallic dry granule glaze, into the kiln for firing. The firing temperature is 1180℃, and the firing time is 45 minutes.
[0061] Step 5. Fine polishing, edge grinding, grading, and packaging. Install 6 sets of grinding brushes for fine polishing.
[0062] Figure 2 This is a rendering of the ceramic tile surface from Example 2. From... Figure 2 As can be seen, the surface of the porcelain tile sample has a silver sand effect. Moreover, the porcelain tile sample prepared in Example 2 has a delicate feel.
[0063] Comparative Example 1
[0064] The process is essentially the same as in Example 1, with the main difference being that a zirconium-free glaze is used instead of the silver sand glaze in step 2. The chemical composition of the zirconium-free glaze includes, by mass percentage: Loss on ignition: 1.8%; SiO2: 57.7%; Al2O3: 31.2%; CaO: 0.8%; MgO: 0.3%; K2O: 3.4%; Na2O: 4.8%. The zirconium-free glaze is applied by pouring, with a specific gravity of 1.84 g / cm³. 3 Glazing amount is 650g / m 2 .
[0065] The zirconium-free glaze in Comparative Example 1 did not contain cobalt black material, and the entire glaze surface was bluish-yellow, failing to reflect the silver sand effect, resulting in only a few scattered sparkles on the tile surface.
[0066] Comparative Example 2
[0067] The process is basically the same as in Example 1, except that in step 3, the flaky mica iron oxide in the silver sand metal dry granule glaze is replaced with granular mica iron oxide, with a diameter-to-thickness ratio of 40.
[0068] The granular mica iron oxide in Comparative Example 2 has a weak silver metallic luster, and when added to the dry granular silver sand glaze, the silver sand effect on the glaze surface is poor after firing.
[0069] Comparative Example 3
[0070] The method is basically the same as in Example 1, with the main difference being that the specific gravity of the silver sand metallic dry granule glaze is 1.32 g / cm³. 3 Glazing amount is 600g / m 2 .
[0071] The amount of silver sand metallic dry granule glaze applied in Comparative Example 3 was too small, making it difficult for the glaze to crystallize and resulting in a weak silver sand effect on the surface of the prepared porcelain tile sample.
[0072] Comparative Example 4
[0073] The method is basically the same as in Example 1, except that the specific gravity of the silver sand metallic dry granule glaze is 1.34 g / cm³. 3 Glazing amount is 900g / m 2 .
[0074] The excessive application of silver sand metallic dry granule glaze in Comparative Example 4 resulted in an overly rounded shape and an arched surface in the prepared porcelain tile sample, which also increased production costs.
[0075] Comparative Example 5
[0076] It is basically the same as Example 1, except that the maximum firing temperature is 1170°C.
[0077] The firing temperature of Comparative Example 5 was too low. Although the surface of the tile had a silver sand effect, the surface was rough and the stain resistance was poor.
[0078] Comparative Example 6
[0079] It is basically the same as Example 1, except that the maximum firing temperature is 1210°C.
[0080] The firing temperature of Comparative Example 6 was too high, which prevented the dry silver sand particles from crystallizing, resulting in a poor surface silver sand effect.
[0081] Comparative Example 7
[0082] It is basically the same as Example 1, with the main difference being:
[0083] Step 2. The mineral composition of the silver sand glaze includes a zirconium-containing glaze and a cobalt black pigment, wherein the mass ratio of the zirconium-containing glaze to the cobalt black pigment is 100:3. The chemical composition of the zirconium-containing glaze includes, by mass percentage: loss on ignition: 1.8%; SiO2: 54.8%; Al2O3: 29.6%; CaO: 0.7%; MgO: 0.3%; K2O: 3.2%; Na2O: 4.5%; ZrO: 5.1%. The mineral composition of the zirconium-containing glaze includes, by mass percentage: potassium feldspar 37%, sodium feldspar 4.5%, nepheline 23%, washed kaolin 8%, quartz 5.5%, calcined alumina 13.5%, and zirconium silicate 8.5%. The chemical composition of the silver sand glaze includes, by mass percentage: Loss on ignition: 1.8%; SiO2: 53.2%; Al2O3: 28.7%; CaO: 0.7%; MgO: 0.3%; K2O: 3.1%; Na2O: 4.3%; ZrO2: 5.0%; CoO: 2.9%. The silver sand glaze is applied by pouring, and its specific gravity is 1.84 g / cm³. 3 Glazing amount is 650g / m 2 .
[0084] The silver sand glaze in Comparative Example 7 contains zirconium, resulting in a higher whiteness of the glaze. This requires the addition of more cobalt black material to achieve the silver sand effect of a zirconium-free glaze, leading to increased production costs and a relatively poorer silver sand effect.
[0085] Comparative Example 8
[0086] It is basically the same as Example 1, with the main difference being:
[0087] Step 3. Mix the dry silver abrasive metal particles and transparent polishing glaze to prepare the silver abrasive polishing glaze. The chemical composition of the dry silver abrasive metal particles includes, by mass percentage: Loss on ignition: 0.6%; Al2O3: 14.2%; SiO2: 41.3%; Fe2O3: 16.8%; CaO: 2.4%; MgO: 0.2%; K2O: 3.1%; Na2O: 2.4%; TiO2: 3.2%; ZnO: 2.8%; P2O5: 7.8%; Li2O: 2.5%; CaF2: 2.7%. The mineral composition of the dry silver abrasive metal particles includes, by mass percentage: 20% potassium feldspar, 10% washed kaolin, 20% quartz, 30% iron phosphate, 6% fluorite, 4% zinc oxide, 6% spodumene, and 4% rutile. The chemical composition of the transparent polished glaze includes, by mass percentage: Loss on ignition: 8.6%; SiO2: 48.6%; Al2O3: 13.2%; CaO: 6.8%; MgO: 3.4%; K2O: 3.8%; Na2O: 2.6%; BaO: 8.5%; ZnO: 4.5%. The silver-sand polished glaze is applied to the surface of the brick after the silver-sand surface glaze has been applied. The silver-sand polished glaze is applied by pouring, with a specific gravity of 1.84 g / cm³. 3 Glazing amount is 650g / m 2 .
[0088] Comparative Example 8: Dry silver abrasive particles were mixed with transparent polished glaze and applied to the surface of tiles after the silver abrasive glaze was applied. After firing, the glaze surface had many pores. The wear resistance was measured at level 3 at 1500 revolutions by the National Ceramic and Plumbing Products Quality Inspection and Testing Center.
Claims
1. A method for preparing a wear-resistant ceramic tile with a silver sand effect on the surface, characterized in that, The preparation method includes the following steps: A silver-sand glaze is applied to the surface of the brick blank; the silver-sand glaze consists of a zirconium-free glaze and a cobalt black pigment, wherein the mass ratio of the zirconium-free glaze to the cobalt black pigment is 100:(2-5); the chemical composition of the zirconium-free glaze includes, by mass percentage: loss on ignition: 1.2%-1.8%; SiO2: 56.4%-60.6%; Al2O3: 28.2%-32.3%; CaO: 0.6%-0.9%; MgO: 0.3%-0.5%; K2O: 3.1%-5.2%; Na2O: 3.2%-4.8%; A silver-sand metallic dry granule glaze is applied to the surface of the brick blank after the application of silver-sand glaze. The composition of the silver-sand metallic dry granule glaze includes flaky mica iron oxide and silver-sand metallic dry granules. The mass ratio of flaky mica iron oxide to silver-sand metallic dry granules is (5~10):(90~95). The chemical composition of the silver-sand metallic dry granules includes, by mass percentage: loss on ignition: 0.5%~0.8%; Al2O3: 14.2%~18.5%; SiO2: 40.1%~4%. 9.3%; Fe2O3: 10.4%~19.6%; CaO: 1.2%~4.3%; MgO: 0.05%~0.5%; K2O: 1.2%~4.4%; Na2O: 1.6%~3. 8%; TiO2: 2.5% ~ 4.5%; ZnO: 2.4% ~ 4.8%; P2O5: 7.2% ~ 14.2%; Li2O: 1.4% ~ 3.6%; CaF2: 2.1% ~ 4.3%; After applying a dry granular glaze of silver sand, the brick blank is fired and polished to obtain a wear-resistant porcelain tile with a silver sand effect on the surface.
2. The preparation method according to claim 1, characterized in that, The aspect ratio of the flaky mica iron oxide is 65~110.
3. The preparation method according to claim 1, characterized in that, The chemical composition of the silver sand metallic dry granule glaze includes, by mass percentage: loss on ignition: 0.6%–1.0%; Al2O3: 12.3%–16.2%; SiO2: 36.2%–46.6%; Fe2O3: 15.7%–25.9%; CaO: 1.2%–3.6%; MgO: 0.05%–0.5%; K2O: 1.4%–3.2%; Na2O: 1.3%–2.8%; TiO2: 1.9%–4.1%; ZnO: 2.1%–4.2%; P2O5: 6.5%–12.5%; Li2O: 1.2%–3.4%; CaF2: 1.8%–3.9%.
4. The preparation method according to claim 1, characterized in that, The silver sand metallic dry granule glaze is applied by pouring; the specific gravity of the silver sand metallic dry granule glaze is 1.30–1.34 g / cm³. 3 The glaze application amount is 750-860 g / m². 2 .
5. The preparation method according to claim 1, characterized in that, The composition of the silver sand metal dry particles includes, by mass percentage: 20%–30% potassium feldspar, 10%–20% washed kaolin, 20%–30% quartz, 20%–40% iron phosphate, 5%–10% fluorite, 4%–10% zinc oxide, 6%–8% spodumene, and 4%–6% rutile.
6. The preparation method according to claim 1, characterized in that, The zirconium-free glaze comprises, by mass percentage: 35%–45% potassium feldspar, 0.1%–5% sodium feldspar, 20%–35% nepheline, 8%–12% washed kaolin, 5%–10% quartz, and 15%–20% calcined alumina.
7. The preparation method according to claim 1, characterized in that, The chemical composition of the silver sand glaze includes, by mass percentage: loss on ignition: 1.4%–2.2%; SiO2: 55.4%–62.3%; Al2O3: 27.8%–31.5%; CaO: 0.6%–1.0%; MgO: 0.2%–0.4%; K2O: 3.2%–5.7%; Na2O: 3.2%–5.8%; CoO: 2.5%–4%.
8. The preparation method according to claim 1, characterized in that, The silver sand glaze is applied by pouring glaze; the specific gravity of the silver sand glaze is 1.82–1.86 g / cm³. 3 The glaze application rate is 600–700 g / m². 2 .
9. The preparation method according to claim 1, characterized in that, The maximum firing temperature is 1180–1200℃, and the firing time is 40–50 minutes.
10. A wear-resistant ceramic tile with a silver sand effect on the surface, characterized in that, The wear-resistant ceramic tile with a silver sand effect on the surface is obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Production process of ceramic tile with high-light and matte precious metal gloss
CN106810297A
Composition for underglaze layer of ceramic articles
SU638577A1